The European Green Deal — More Than Climate Neutrality - Sarah Wolf; Jonas Teitge; Jahel Mielke; Franziska Schütze; Carlo Jaeger (Intereconomics)
Abstract The European Green Deal aims at climate neutrality for Europe by 2050, implying a significant acceleration of emission reductions. To gain the necessary support, it needs to reduce regional and social inequalities in Europe. We present objectives in terms of jobs, growth and price stability to complement the emission reduction targets and sketch a proof-of-concept investment profile for reaching these goals. Substantial additional annual public investments, of about 1.8% of pre-COVID-19 GDP, are proposed for the next decade. Their allocation includes retrofitting the European building stock, consciously fostering a renewal of the European innovation system as well as complementary measures in the fields of education and health. The scenario outlined in this article is meant as an input to the urgently needed discussion on how the European Green Deal can shift the EU economy to a new development path that realises a carbon-neutral Europe by 2050 while strengthening European cohesion.